2019
DOI: 10.1136/jim-2018-000970
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography correlations between anthropometrical parameters in kidney transplant recipients

Abstract: Ultrasound elastography (USE) is a method to assess the stiffness of parenchymatous organs. Shear wave elastography (SWE) is considered to be the most suitable elastography method for the non-invasive kidney transplant (KTx) elasticity assessment. The aim of this study was to assess the implementability of SWE for the evaluation of kidney transplant elasticity measurement depending on the depth of an allograft, body mass index (BMI) and donor age. Secondly, to investigate the associations between SWE stiffness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Ma et al reported significantly (p-values < 0.03) positive correlations of cortical (0.26) and medullary stiffness (0.59) with interstitial fibrosis [23]. Järv et al [37] have also reported the association between the cortex and medulla allograft stiffness and body mass index, with lower mean SWE values on overweight or obese patients (p-value = 0.006), a similar result being also found in our cohort.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Ma et al reported significantly (p-values < 0.03) positive correlations of cortical (0.26) and medullary stiffness (0.59) with interstitial fibrosis [23]. Järv et al [37] have also reported the association between the cortex and medulla allograft stiffness and body mass index, with lower mean SWE values on overweight or obese patients (p-value = 0.006), a similar result being also found in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…We conducted this study to examine the intra-and inter-examinations variability of kidney allografts SWE stiffness as an additional tool in post kidney transplantation evaluation. The patients included in our cohort had similar demographic characteristics in terms of age and gender with the patients investigated by Ma et al [23], but are younger as compared to those investigates by Järv et al [37].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Nicolas Grenier observed that renal stiffness measured by supersonic shear imaging (SSI) had no correlation with baseline characteristics ( p > 0.05) [ 28 ], which is consistent with our results. However, Järv et al [ 29 ] reported that renal stiffness had negative correlations with age (r = −0.2, p = 0.03) and BMI (r = −0.3, p = 0.01). The reason why their result is different from ours may be that Järv et al included more patients who were more than 5 years post renal transplantation, a group which only accounted for 30% of the patients in our study.…”
Section: Discussionmentioning
confidence: 99%